2005
DOI: 10.1520/jai12517
|View full text |Cite
|
Sign up to set email alerts
|

ASTM C 88 Test on Soundness of Aggregate Using Sodium Sulfate or Magnesium Sulfate: A Study of the Mechanisms of Damage

Abstract: In this study, the mechanisms of damage to aggregate particles by sodium sulfate and magnesium sulfate solutions were investigated. By using glass and aluminum containers to represent aggregate pore space and confining walls, test results showed that during soaking cycles crystal growth occurred that applied some bearing pressure on the container. This bearing pressure, however, was secondary to more damaging pressure that occurred during the oven drying cycles. During soaking cycles, mirabilite (Na2·SO4 10H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Although not found in this study, Na 2 SO 4 could potentially exist in the heptahydrate form, usually indicated by a band at 989 cm –1 , or in the decahydrate form with a band at 988 cm –1 . , The presence of anhydrous Na 2 SO 4 formed at 95 °C in this work is consistent with another report that mentioned the formation of anhydrous Na 2 SO 4 at high temperatures . Furthermore, the peak position of Na 2 SO 4 at 994.80 cm –1 in an SO 4 2– /Li + ratio of 2 closely resembles the band of thenardite, which possesses an orthorhombic crystal structure .…”
Section: Resultssupporting
confidence: 91%
“…Although not found in this study, Na 2 SO 4 could potentially exist in the heptahydrate form, usually indicated by a band at 989 cm –1 , or in the decahydrate form with a band at 988 cm –1 . , The presence of anhydrous Na 2 SO 4 formed at 95 °C in this work is consistent with another report that mentioned the formation of anhydrous Na 2 SO 4 at high temperatures . Furthermore, the peak position of Na 2 SO 4 at 994.80 cm –1 in an SO 4 2– /Li + ratio of 2 closely resembles the band of thenardite, which possesses an orthorhombic crystal structure .…”
Section: Resultssupporting
confidence: 91%
“…Only a few mirabilite could have nucleated since only a limited amount of oven-dried thenardite dissolved during the destructive immersion regime. This is because a shell of mirabilite encapsulates thenardite, thereby preventing rapid dissolution and further hydration of thenardite if the latter is large enough (Haynes 2005;Linnow et al 2006). Another possible reason is that the metastable heptahydrate might have precipitated in TS in preference to the more destructive mirabilite.…”
Section: Possible Reasons For Sodium Sulphate Inefficacymentioning
confidence: 99%
“…H 2 O) to epsomite (MgSO 4 . 7H 2 O) transformation (Correns & Steinborn 1939;Chatterji & Jensen 1989;Haynes 2005). Therefore, the hydration pressure hypothesis has been ruled out as a credible cause of salt damage (Thaulow & Sahu 2004).…”
mentioning
confidence: 99%
“…The remaining samples obtained 2.5%, 1.1%, 0.9%, 0.7%, and 0.5%. The values of all the samples fell within the limit range of less than 12%, as recommended in ASTM C-88 [39]. Therefore, the samples of artificial LWA had an acceptable loss of soundness to resist changes in volume under the subjected condition.…”
Section: Mechanical Propertiesmentioning
confidence: 54%